KYIVMOHYLA ACADEMY AS CITADEL OF SPIRITUALITY AND EUROPEAN EDUCATION INTHE CONTEXT OF METAHISTORY - Kovalchuk, N. (Continuing Professional Education: Theory and Practice, 2019)
In the article the spiritual and educative activity of KyivMohyla academy in the context of metahistory in light of the main archetypes of the Ukrainian culture (archetype of word, archetype of the ethical value of free individuality, archetype of sophity and archetype of heart. The purpose of this article is to consider cultural and educational activities of KyivMohyla Academy in the context of archetypes of Ukrainian culture. In order to solve this problem the author has observed following items: how the archetype of the word influences the high mission of Kyiv Mohyla Academy; how the archetype of the free personality‘s moral values reveals in the organization and training activities of the Kyiv Mohyla Academy; the view of the archetype of the sophity on the cultural and educational activities of KyivMohyla academy; the content of the archetype of heart in the context of the philosophical concepts of H. Skovoroda etc.